The Effect Word of Mouth on Saving Intention Through Brand Image as an Intervening Variable - Kharisma Yussitha; Irmayanti Hasan; Yayuk Sri Rahayu (Syarikat: Jurnal Rumpun Ekonomi Syariah, 2023)
Word of mouth and brand image are factors in forming someone's intention to use a product. This condition requires the company to continue to provide comfort for every use of its products. The purpose of this study was to examine the direct effect of word of mouth on the intention to save through the BMT Alhikmah brand image. This study uses a quantitative method with the help of SmartPLS software to assist data analysis. The sample approach used was simple random side by way of distributing questionnaires and collecting 95 respondents. The results of this study indicate that word of mouth has a direct effect on saving intention. The involvement of word of mouth also has a direct effect on brand image, whereas brand image has no direct influence on the intention to save at BMT Alhikmah. In addition, the results of this study indicate that word of mouth does not have a direct effect on saving intention through brand image as an intervening variable. The research weakness lies in the brand image variable which does not have a direct effect on the intention to save BMT Alhikmah.